Chronic diseases of lifestyle risk factor profiles of a South African rural community - Mukadas O, Akindele; Ushotanefe Useh (AOSIS, 2021)
Globally, chronic diseases of lifestyle account for millions of dollars spent annually on health. These diseases share similar risk factors including: physical inactivity, obesity, cigarette smoking, and hypertension among others. This study sought to assess risk factors for chronic diseases of lifestyle of a rural community in South Africa. This study used a survey design with data randomly collected using the WHO STEPS Instrument for Chronic Disease Risk Factor Surveillance from participants who attended routine checks from February to October 2018 from a trained healthcare practitioner. Informed consent was sought from all participants before the administration of the instrument. The research setting was the community Primary Health Center. About 54.0% of participants presented with no family history of hypertension but 19.7% had a family history of type II diabetes mellitus. More women were found to be hypertensive, with the majority (93.4%) monitoring their blood pressure. The study revealed that more men were current smokers. A large number of participants were engaged in a sedentary lifestyle with about one-third of the participants reported being obese. Physical inactivity, sedentary lifestyle, and hypertension were among the lifestyle-related risk factors for chronic diseases among residents of this rural community.